Perancangan Aplikasi Boardingpass Online untuk Melatih Kedisiplinan Siswa SMKN 3 Salatiga - Andre Setyawan; Adriyanto Juliastomo Gundo (Peneliti.net, 2021)
Discipline is part of achieving the goals of education in Indonesia. As a result of the COVID pandemic, student discipline is not monitored due to distance learning. especially at SMK 3 Salatiga which has a boarding pass system to train and monitor student discipline but cannot run due to the pandemic. The purpose of this research is to create an application to train and monitor student discipline on the basis of the old boardingpass system. after this application is completed using the prototype method, it will be tested for feasibility with the ISO 9126 standard. This application is expected to meet the standards of ISO 9126 so that it can be applied at SMK 3 Salatiga in order to help teachers monitor their students. respondents in the application test are a software engineer, teacher, student and admin of smk 3 salatiga. The results of testing this application using a questionnaire based on aspects of ISO 9126, namely aspects of functionality, usability, efficiency, and portability show that each aspect gets the